Multilateral trade measures in a post-2012 climate change regime? What can be taken from the Montreal Protocol and the WTO? - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2009)
The climate-trade nexus gains increasing attention as governments are taking great efforts to forge a post-2012 climate change regime to succeed the Kyoto Protocol. This raises the issues of the scope of trade-related measures and of when and how they could be used. This paper discusses how far trade-related measures should be incorporated in that context. Drawing on an analogy to the Montreal Protocol and comparing developing country's climate mitigation and adaptation needs with the funding available, the paper argues that such measures should initially be applied only among Annex I or II countries. To discipline the use of unilateral trade measures at the international level, the paper emphasizes a need to define comparable climate efforts. Moreover, the Lieberman-Warner bill in the U.S. Senate - taken as a proxy for future U.S. climate legislation - is assessed, and found to be neither effective nor likely to be WTO-consistent. The paper is concluded by arguing that, in order to encourage developing countries to do more to combat climate change, developed countries should focus on carrots. Sticks can be incorporated, but only if they are credible and realistic and serve as a useful supplement to push developing countries to take actions or adopt policies and measures earlier than would otherwise have been the case.
Keywords: F18; Q48; Q54; Q56; Q58; 330; Post-2012 climate negotiations; Trade-related measures; Lieberman-Warner bill; WTO; Montreal Protocol; Developing countries; United States